ANALYSIS OF SOCIAL ASSISTANCE FUND CORRUPTION IN CORRELATION WITH LAW ENFORCEMENT - Gerardus Revin Tjahja; Melda Maritza Permana; Hosea Noel Calvian; Muhammad Iqbal Ibrahim; Muhammad Iqbalfarrelzy Althafah Kesuma; Justin William Setiawan (President University, 2022)
Corruption is an attempt to intervene using abilities obtained from a position including information, decisions, influence, money, and/or wealth for the benefit and benefit of thinking for oneself. Social assistance is the assistance in the form of money and/or goods to individuals, families, groups, and/or communities which is not continuous and selective to protect against the possibility of social risks. Social assistance funding should be distributed to those who need it. However, some irresponsible parties took the money only for their interests. The legal problems we found here are 1) the social assistance fund was later found to be corrupted by the government, and 2) the legal enforcement from the KPK was not bold enough to resolve the case. The case of corruption in social assistance funds (bansos) for handling the COVID-19 pandemic involving state officials has caused public unrest and disappointment. This research aims to analyze the factors behind the occurrence of corruption, its impact on the economy and community welfare, as well as legal efforts and prevention or solutions.Keywords: Corruption; Corruption Eradication Committee; Legal Enforcement; Social Assistance;